Women of Color and Religious Mysticism in Southern Gothic - Ho, Elizabeth (Auckland University of Technology, 2018)
The exegesis, Women of Color and Religious Mysticism in Southern Gothic, doesn’t just frame Rituals of the Night but amplifies it, particularly to give silenced voices a chance to speak within the genre. The exegesis explores two major themes present within Rituals of the Night from the very first pages of the first draft – the role and lives of women of color and religious mysticism in Southern Gothic. The exegesis is placed before the creative because Rituals of the Night is atypical and clarity must be sought before it can be read. The creative thesis, Rituals of the Night, conjures forth a Southern gothic story of Louisa, a young black woman, in the Southern United States in the 1940s. Like a periscope, it peers into different ways of living – as a minority, as a white person, as an outsider, as a worshipper. Infused with haunting elements, it takes on the challenge of finding out just what it means to be a woman of color in the white man’s world.
Keywords: American Southern Gothic; African American women; Fiction; Women of color and religious mysticism